Markets, mobs & mayhem : - Menschel, Robert (John wiley & Sons, 2002)
"Its easy to understand the excesses of the 90s by reading Bob Menschels captivating, well-written history of the ways investors have been victimized by greed, folly, and chicanery. This is a fascinating chronicle of improbable manias that set off frenzied and thoughtless buying." --Arthur Levitt, former chairman, Securities and Exchange Commission "This books light-hearted, level-headed insights may be directed at the business world, but they ring equally true for government and public officials. Robert Menschel gives a valuable perspective on the power of the crowd." --Senator Charles E. Schumer "This wonderfully witty and wise book by one of the most successful investors Ive ever known is a must-read. He reminds us that trees do not grow in the sky and that if it looks too good to be true, it is." --John C. Whitehead, former chairman, Goldman Sachs & Co. and Chairman, Lower Manhattan Development Corp. "This timeless anthology on the madness of crowds is chock-full of worldly wisdom, relevant anecdotes, and wonderful quotations, interlaced with the light touch of our finest cartoonists. Coming as it does in the aftermath of the great stock market bubble, Bob Menschels fine book is also a useful reminder of what we all knew, deep down, but were afraid to admit: When the perception of stock prices loses its linkage to the reality of corporate values, a day of reckoning always follows." --John C. Bogle, founder and former CEO, The Vanguard Group "This highly entertaining book is must reading for everyone without exception, regardless of age, wealth, or political persuasion. Menschels delectable presentations expose the very roots of human behavior in a variety of fascinating situations, familiar and unfamiliar. Dont skim; read every word." --Peter Bernstein, author of The Power of Gold: The History of an Obsession and Against the Gods: The Remarkable Story of Risk